An Examination of Physical and Chemical Attributes of soil in the Vicinity of Industrial and Agricultural Zone in Jaipur - Aisha Rafi; Jhalak Agrawal; Bhumika Maheshwari; Manah Yadav (International Journal of Pollution: Prevention & Control, 2025)
This research paper examine the complex relationship among urbanization ,agriculture, and soil conservation in Jaipur , Rajasthan, with a specific focus on the Industrial Area. Utilizing a multidisciplinary approach, the study comprehensively examines soil health through extensive field studies and meticulous soil analysis. Central to the investigation is the evaluation of industrial activities' impact on soil quality, aiming to highlight challenges and propose integrated strategies for sustainable soil management. The findings underscore the critical importance of addressing industrial influences on soil health and advocate for proactive measures to mitigate adverse effects. By offering insights into the dynamic relationship between industrialization and soil conservation, the research contributes valuable recommendations tailored to the unique context of Jaipur. These recommendations prioritize site- specific soil conservation practices, aimed at fostering environmental sustainability and fostering responsible industrial development in the region. Through informed decision-making and collaborative efforts, the study endeavors to pave the way for a harmonious balance between urban growth, agricultural needs, and soil preservation in Jaipur
Keywords: Agricultural zones; Industrial zones; Soil analysis; soil properties